Development of the Augmented Reality Model (DISMUS) as Social Studies Digital Learning Media - Ade Budhi Salira; Dina Siti Logayah; Rizal Akbar Darmawan; Kirani; Tri Tianti (heritage, 2022)
Development of augmented reality as a learning medium that can present real but virtual-based visuals. Augmented reality gives students a sense of embodiment, enabling them to recall experiences in the real and virtual worlds. Based on this, the literature the initiative to develop an augmented reality-based application called dismus by working with virtual objects such as 3D models combined with audio. However, in the development that has been carried out, it is necessary to have discussion sessions through focus group discussions so that the applications that have been developed can reach the trial stage. The result of this focus group discussion is that the dismus application has successfully entered the innovation stage as a learning medium that can be used in the classroom with some inputs to keep the user's comfort in mind.